Sistem Otomasi Rumah Berbasis Logika Fuzzy Menggunakan Arduino Uno R3 Untuk Mengoptimalkan Penggunaan Listrik - Heriyanto Antony; Sean Coonery Sumarta (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2017)
This research focuses on the manufacture of home automation systems to optimize the use of electricity. Home automation system has four features, namely automatic control, manual control, control based on the habits and customs control based on fuzzy logic and method Tsukamoto. Fuzzy logic Tsukamoto will calculate the temperature that should be spent by the AC, using input from sensors LM35 that are indoors and outdoors, so that the temperature of the issued AC was not too hot and too cold home automation system features 3 sensors which PIR sensor, sensor LM35 and LDR sensor that will be used as input data on the system. Home automation system will control electrical equipment, namely air conditioning and lighting optimally.